Digital Economy Multiplier - Vladimir V. GLINSKIY; Lyudmila K. SERGA; Leonid K. BOBROV; Mikhail A. ALEKSEEV; Kirill A. ZAYKOV; Yuliya N. ISMAIYLOVA (Communications of International Proceedings, 2021)
The article considers approaches to assessing the contribution of the digital economy to the national product from the perspective of the country and the region. At the regional level, it is proposed to calculate the multiplier effect of digital activities, using the multiplier. A methodology for estimating the digital economy multiplier is proposed, and the specifics of its calculation for an individual region are discussed. Data from the Federal State Statistics Service are used as the information base. The reported study was funded by the Siberian Institute of Management – branch of the Russian Presidential Academy of National Economy and Public Administration.
Keywords: Digital Economy Multiplier; Multiplier Effect of Digital Economy; Results; Evaluation Methodology.